John Stuart Mill and Fourierism: 'association', 'friendly rivalry' and distributive justice. (2nd January 2019) - McCabe, Helen
ABSTRACT: John Stuart Mill's self-description as 'under the general designation of Socialist' has been under-explored. It is an important feature of something else often overlooked: the importance of the French context of Mill's thought. This article focuses on the role of Fourierism in the development of Mill's ideas, exploring the links to Fourierism in Mill's writing on profit-sharing; his use of the words 'association' and 'friendly rivalry'; and his views concerning distributive justice. It then reconsiders his assessment of Fourierism as a desirable, workable and immediately implementable form of social reform, ultimately arguing it was Mill's most-preferred form of 'utopian' socialism.